Neuro-linguistic programming workbook for dummies - Ready, Romilla (--For dummies., 2008)
If you are one of the millions of people who have already discovered the power of NLP, Neuro-linguistic Programming Workbook For Dummies will allow you to perfect its lessons on how to think more positively and communicate more effectively with others. This workbook is packed with hands-on exercises and practical techniques to help you make the most of NLP's toolkit for new thinking and personal change. These can have an impact on many aspects of your life: from helping you change your negative beliefs, to building rapport and influencing others, to taking charge of the direction your life is.